Catecholamines and their O-methylated metabolites in vitreous humor in hypothermia cases - Hervet, Tania; Teresiński, Grzegorz; Hejna, Petr; Descloux, Emilienne; Grouzmann, Eric; Palmiere, Cristian (Forensic science, medicine, and pathology, 2016)
PURPOSE: The aim of this study was to assess the diagnostic value of catecholamines and their O-methylated metabolites in vitreous humor samples in identifying antemortem cold exposure and fatal hypothermia in the forensic casework. METHODS: A total of 80 autopsy cases (40 hypothermia fatalities and 40 cases in which hypothermia as the main or contributory cause of death was excluded) were selected for this study. Catecholamines and their O-methylated metabolites were measured in urine and vitreous humor samples collected at autopsy. RESULTS: Urine catecholamine and their O-methylated metabolite concentrations were significantly higher in hypothermia-related deaths. On the other hand, measurements in vitreous humor samples did not reveal statistically significant differences between hypothermia-related deaths and controls. CONCLUSIONS: Globally considered, our findings seem to suggest that, contrary to urine catecholamines and their O-methylated metabolites, vitreous levels of these compounds appear to be of limited value in characterizing human antemortem stress reactions due to cold exposure and can hardly be used in the forensic setting to support the diagnosis of hypothermia.
Keywords: Hypothermia; Normetanephrine; senioři; adrenalin; noradrenalin; Female; Male; mladý dospělý; Metanephrines; metanefrin; normetanefrin; Aged; dopamin; Middle Aged; Postmortem Changes; Young Adult; hypotermie; posmrtné změny; Vitreous Body; soudní patologie; Metanephrine; katecholaminy; mužské pohlaví; ženské pohlaví; Adult; Epinephrine; Catecholamines; Vitreous humor; dospělí; lidé středního věku; Forensic Pathology; studie případů a kontrol; Dopamine; lidé; Humans; sklivec; Postmortem biochemistry; Norepinephrine; Case-Control Studies